2023
DOI: 10.1037/emo0001089
|View full text |Cite
|
Sign up to set email alerts
|

EmoSex: Emotion prevails over sex in implicit judgments of faces and voices.

Abstract: Appraisals can be influenced by cultural beliefs and stereotypes. In line with this, past research has shown that judgments about the emotional expression of a face are influenced by the face’s sex, and vice versa that judgments about the sex of a person somewhat depend on the person’s facial expression. For example, participants associate anger with male faces, and female faces with happiness or sadness. However, the strength and the bidirectionality of these effects remain debated. Moreover, the interplay of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
2
4
0
Order By: Relevance
“…Furthermore, other studies have demonstrated that experience with acoustic stimuli influences how the stimuli are processed (Demirkaplan & Hacıhabiboğlu, 2020;Wisniewski et al, 2012). Finally, previous studies found evidence for stereotypic beliefs and influences of gender on the perceived expression of vocal affect (Bonebright et al, 1996;Korb et al, 2023). These results are in line with our findings that the effect of affective voice was more pronounced for male voices played at high intensities.…”
Section: Listener's Expectations Influence Distance Perception Of Aff...supporting
confidence: 92%
“…Furthermore, other studies have demonstrated that experience with acoustic stimuli influences how the stimuli are processed (Demirkaplan & Hacıhabiboğlu, 2020;Wisniewski et al, 2012). Finally, previous studies found evidence for stereotypic beliefs and influences of gender on the perceived expression of vocal affect (Bonebright et al, 1996;Korb et al, 2023). These results are in line with our findings that the effect of affective voice was more pronounced for male voices played at high intensities.…”
Section: Listener's Expectations Influence Distance Perception Of Aff...supporting
confidence: 92%
“…The formula of the model was: choice ~ emotion + fNMES + ambiguity + emotion: fNMES + emotion: ambiguity + ambiguity:fNMES + (1 | Participant). For a similar analysis, see Korb et al (2023).…”
Section: Data Preparation and Analysesmentioning
confidence: 93%
“…All emotion changes were based on the Facial Action Coding System (FACS; Ekman et al, 2002) by a certified FACS coder using FacsGen. For similar procedures, see Korb et al (2022).…”
Section: Stimulimentioning
confidence: 99%
“…Remarkably, a higher RM for happy-to-ambiguous (compared to angry-toambiguous) faces was mainly found in male avatars, with female avatars instead leading to similar RM magnitudes in both emotion conditions. This effect of sex can reveal internalized cultural or social statistical regularities, with male conspecifics being perceived as either more aggressive or observers being more prone to further anticipate angry and threatening states in males (Harris et al, 2016;Korb et al, 2022;Korb & Massaccesi, 2020). For instance, a study using a set of static avatar faces, varying along the emotion dimension (angry-to-happy) and sex dimension (male-to-female), found that sex features influenced emotion categorization and rating predominantly when the emotional expression was ambiguous, with more masculine faces being judged as angrier ("maleness-anger" association) and faces with more female features being judged as happier ("femalenesshappiness" association) (Korb et al, 2022).…”
Section: Increased Anticipation Of Threatmentioning
confidence: 99%
See 1 more Smart Citation